Systems’ Librarians: Unidentified but Essential in Nepalese Libraries - Singh, Sanjiv Kumar; Nyaichyai, Lila (Access: An International Journal of Nepal Library Association, 2023)
Digital library dealt with information communication technology (ICT) infrastructures that is different from manual library infrastructure. Digital library is the growing demand in contrast to manual library, which demanded for systems' librarians or digital librarians. The collected data from seven libraries in Nepal to examine the availability of Systems' librarian manpower provided no light of hope. Those libraries were selected using convenient judgmental sampling through a short interview with currently available librarians about the concept of a Systems' librarian. Digitally skilled and responsible for digital data management personnel was defined as systems' librarians who have the necessary knowledge and skills in library software, networking, data entry, and troubleshooting of ICT-related issues. The study found that out of the seven libraries, only two had systems' librarians, yet their designation was not pin-pointedly named as' systems' librarian'. While others lacked the required manpower. The study also revealed that there were no Systems' Librarians in any of the libraries. The respondents' attitudes and perceptions towards the Systems' Librarian concept varied, with some accepting it as adaptable, acceptable, and appreciable. The study recommended for the recruitment of Systems' Librarians in Nepal as the library’s resources adopted the concept of paperless and library-without-wall. The lack of concerned manpower to look after electronic resources could lead to serious problems, and it's time for the Nepal Library Association and stake holders to advocate for the specialized manpower for the post of Systems' Librarian (also called digital librarian) and generate skilled manpower.